L’utilisation de la pierre dans la construction rurale en Normandie aux époques médiévale et moderne - Laurent Dujardin (In Situ)
The use of stone in Normandy’s old rural buildings is not well documented. These uses vary widely from one part of the province to another. The method applied to study these uses was to articulate the study on the material itself and its quarry origins, to observe the old rural buildings in the field and to confront these observations with written sources (‘tabellionnages’, land registers, narrative sources, building accounts…) and with archaeological evidence. Although many considerations are at play in the use and provenance of the stones, it is clear that when geology permitted it, local resources were used whenever possible for the structural walls. Alongside stone quarries which supplied one or several parishes, other quarries produced higher quality stone and finished or semi-finished products. Finally, for certain specific uses, rural construction used stones from further afield, produced and commercialised at a few centres.